2012
DOI: 10.1007/s11010-012-1266-2
|View full text |Cite
|
Sign up to set email alerts
|

Fhl1 as a downstream target of Wnt signaling to promote myogenesis of C2C12 cells

Abstract: Previous studies have shown that Wnt signaling is involved in postnatal mammalian myogenesis; however, the downstream mechanism of Wnt signaling is not fully understood. This study reports that the murine four-and-a-half LIM domain 1 (Fhl1) could be stimulated by β-catenin or LiCl treatment to induce myogenesis. In contrast, knockdown of the Fhl1 gene expression in C2C12 cells led to reduced myotube formation. We also adopted reporter assays to demonstrate that either β-catenin or LiCl significantly activated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 53 publications
3
30
0
Order By: Relevance
“…FHL-1 contains a TCF/LEF binding site, which can be stimulated by b-catenin or Wnt pathway agonist lithium chloride inducing muscle hypertrophy and repressing chondrogenesis. [59,60]. In support of our results, a recent study [61] identified that overexpression of FHL1 in murine MC3T3-E1 cells promotes osteogenesis.…”
Section: Discussionsupporting
confidence: 89%
“…FHL-1 contains a TCF/LEF binding site, which can be stimulated by b-catenin or Wnt pathway agonist lithium chloride inducing muscle hypertrophy and repressing chondrogenesis. [59,60]. In support of our results, a recent study [61] identified that overexpression of FHL1 in murine MC3T3-E1 cells promotes osteogenesis.…”
Section: Discussionsupporting
confidence: 89%
“…Myoblasts isolated from two EDMD patients harbouring the X281E and K157VfsX46 mutations investigated here exhibit reduced expression of mutant FHL1 and delayed myoblast differentiation (Gueneau et al, 2009). Similarly, shRNA-mediated knock-down of FHL1 impairs myotube formation in vitro (Lee et al, 2012). FHL1 expression is decreased in animal models of disuse atrophy (Loughna et al, 2000), and FHL1 protein expression might be reduced in SPM, XMPMA and RSS, which might further exacerbate the loss of normal FHL1 function caused by mutation.…”
Section: Discussionmentioning
confidence: 81%
“…The four and a half LIM domain protein 1 (FHL1) is highly expressed in skeletal and cardiac muscle (Lee et al, 1998;Brown et al, 1999;Greene et al, 1999;Morgan and Madgwick, 1999), influencing cellular architecture (McGrath et al, 2003;McGrath et al, 2006), myoblast differentiation (Lee et al, 2012), mechanotransduction (Sheikh et al, 2008) and skeletal-muscle fibre size . FHL1 mediates protein-protein interactions through its LIM domains; cysteine-rich double zinc fingers containing the consensus sequence [CX2CX16-23HX2C] X2 [CX2CX16-21CX2(C/H/D)] that facilitate binding to proteins but not DNA (Schmeichel and Beckerle, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…It is important to point out that the mesenchymal markers of airway reactivity chosen by us are markers of myofibroblast differentiation (a-SMA and calponin), a hallmark of chronic lung diseases, such as asthma, and/or have been shown to have increased matrix deposition (fibronectin and collagen III) in the subepithelial space of the airways in asthma (18)(19)(20). Furthermore, the other markers used by us, such as b-catenin and LEF-1, are functional intermediates in the Wnt signaling pathway, a key mediator of myogenesis, justifying their inclusion in our analysis (21)(22)(23). However, it must be pointed out that, in our analysis of the myogenic markers of airway reactivity by both Western blotting and immunofluorescence, we did not differentiate between the mesenchymal and vascular compartments.…”
Section: Discussionmentioning
confidence: 89%